Peran Coenrad Laurens Coolen sebagai Pemimpin Desa Kristen Ngoro Jombang 1827-1844 serta Nilai-Nilai Edukasinya - Bastyan, Habiby; Jati, Slamet Sujud Purnawan (Kamaya: Jurnal Ilmu Agama, 2024)
Historical studies often reveal the role of figures in shaping the thought patterns and behavior of past people. One interesting example is Coenrad Laurens Coolen's role as the leader of the Ngoro Christian Village in Jombang. In 1827-1844, coenrad laurens coolen, a half-Javanese European, formed the Ngoro Christian Village. Coolen played the role of leader of the Ngoro Christian Village. Apart from developing the village's physical infrastructure, Coolen also strengthens the community's spiritual dimension with humanist Christian teachings. Coolen understands Javanese society and teaches Christian teachings using a Javanese cultural approach. This means that Coolen was not only a pioneer of Christian teaching in Java, but also combined these teachings with Javanese culture, making it more easily accepted by the local community. The research method used in writing this article is a historical research method with a descriptive qualitative approach to investigate the role of Coenrad Laurens Coolen as leader of the Ngoro Christian Village and the educational values ​​reflected in this process. Coenrad Laurens Coolen played an important role in the Christian Village of Ngoro, Jombang, from 1827 to 1844. It was found that Coolen, who had a Dutch-Javanese background, made it easier for him to spread Christianity through a Javanese cultural approach. Coolen played a role in developing Ngoro Village physically and spiritually, as well as educational values ​​in his leadership that are in accordance with the six dimensions of the Pancasila Student Profile, namely faith and noble character, global diversity, mutual cooperation, independence, critical reasoning, and creativity. Coenrad Laurens Coolen's role as leader of the Ngoro Christian Village in Jombang from 1827 to 1844 shows educational values ​​that are relevant to the Pancasila Student Profile. So Coenrad Laurens Coolen's role as leader of the Ngoro Christian Village in Jombang from 1827 to 1844 can be used in history learning at school.